Theoretical investigations of structural, electronic, optical and thermoelectric properties of oxide halide perovskite ACoO3 (A=Nd, Pr or La). (1st April 2022) - Absike, H.; Baaalla, N.; Attou, L.; Labrim, H.; Hartiti, B.; Ez-zahraouy, H.
Abstract: Perovskite oxides have emerged as promising alternatives for photovoltaic devices due to their astonishing optoelectronic properties. Nevertheless, a density functional theory study was performed on the electronic, optical, and thermoelectric properties of ACoO3 (A = Nd, Pr, and La) by TB-mBJ potentials. Based on the optimized structures, the observed results show that studied compounds display p-type semiconductor behavior with a bandgap of 1.95 eV, 1.08 eV, and 1.57 eV respectively. Hence, spherical charge density contours illustrate the ionic character of Nd/Pr/La/Co and O. The optical spectra are reported and discussed, the maximum absorption intensity for the LaCoO3 is ∼20 × 10 4  cm around 400 nm. Furthermore, the figure of merit, the electrical and thermal conductivity of each compound are investigated by applying Boltzmann transport theory, the high mobility of carriers enhances the Seebeck coefficient and electrical conductivity of ACoO3 (A = Nd, Pr, and La) materials. Our finding results make these materials favorable candidates for photovoltaic applications. Highlights: First-principles method was used to study the structural, electronic, optical and thermoelectric properties of oxide halide perovskite ACoO3 (A = Nd, Pr or La). The bandgap values of LaCoO3 and NdCoO3 are suitable for photovoltaic, optoelectronic devices. The studied oxide halide perovskite ACoO3 (A = Nd, Pr or La) show excellent light absorption in the visible range. The NdCoO3 exhibit high electrical conductivity.